Cannabidiol regulates apoptosis and autophagy in inflammation and cancer: A review - Fu, Ze; Zhao, Peng-Yue; Yang, Xing-Peng; Li, Hao; Hu, Shi-Dong; Xu, Ying-Xin; Du, Xiao-Hui (Frontiers in Pharmacology, 2023)
Cannabidiol(CBD) is a terpenoid that widely exists in natural plants. After purification, it is used as a compound in the treatment of mental diseases, mainly with anti-depressive, anxiolytic, and antiepileptic effects. In recent years, evidence has indicated a role for CBD in the regulation of cellular pathophysiological processes, including autophagy, cytokine secretion, apoptosis, and regulation of innate and adaptive immune responses. Despite these advances, current research data demonstrate contradictory findings with regard tu not only the magnitude of CBD-mediated effects, but also to the direction of the effects. For example, different data indicate that CBD treatment can increase, decrease or have no significant effect on autophagy and apoptosis. Differences between studies in biological models, cell types, and the ratio of CBD concentration to solution may explain the differences in results. This reviews focuses on the mechanism of CBD's regulation of autophagy and apoptosis in inflammatory response and cancer, focusing on the broad prospects of CBD for anti-inflammatory response and cancer therapy in the future.